2004
DOI: 10.1039/b407760c
|View full text |Cite
|
Sign up to set email alerts
|

Elastomer-glass micropump employing active throttles

Abstract: We report a reciprocating microfluidic pump, the Micro Throttle Pump (MTP), constructed in a relatively uncomplicated manner from glass and microstructured poly(dimethylsiloxane)(PDMS). Unconventionally, the MTP employs throttling of fluid flow as distinct from fully-closing valve structures. Accordingly, this technique offers the prospect of solid-phase suspension tolerance. The reported MTP employs piezoelectrically (PZT) actuated deformation of flow constrictions (throttles) fabricated from PDMS at the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 19 publications
0
22
1
Order By: Relevance
“…As previously reported, 18 microthrottle pumps ͑MTPs͒ were developed to utilize "throttling," the use of variable cross-section flow-constrictions ͑microthrottles͒ to control fluid flow. 19 A detailed discussion of microthrottles, their application in microthrottle pumps, and the operating principles of microthrottle pumps has been made previously, 20 therefore only a brief summary is provided here.…”
Section: B Microthrottle and Mtp Operating Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously reported, 18 microthrottle pumps ͑MTPs͒ were developed to utilize "throttling," the use of variable cross-section flow-constrictions ͑microthrottles͒ to control fluid flow. 19 A detailed discussion of microthrottles, their application in microthrottle pumps, and the operating principles of microthrottle pumps has been made previously, 20 therefore only a brief summary is provided here.…”
Section: B Microthrottle and Mtp Operating Principlesmentioning
confidence: 99%
“…Molds were microfabricated from SU8 ͑Microchem Corp., MA, USA͒ structural photoresist on silicon wafers. The PDMS microstructures were then cast in Dow Corning Sylgard, ® MI, USA͒ 184 PDMS processed in the, previously reported, 18 standard way ͑Fig. 2͒.…”
Section: Fabrication and Assemblymentioning
confidence: 99%
“…thermore, silicon, glass, polymer, and elastomer-based microvalves or throttles have been developed utilizing piezoactuators [11][12][13][14]. Piezoelectric valves are moderately easy to manufacture and provide a comparatively high stroke and actuation force and fast mechanical response [15].…”
Section: Introductionmentioning
confidence: 99%
“…Here, various structures of piezoelectric actuator driven micropumps are described. In particular, we found that recently introduced piezoelectric microthrottle (MT) pumps provide good performance [36]. These devices are based on throttle valves which do not completely close during operation but rather exhibit sequential openings and closings gated by piezoelectric actuators.…”
Section: Introductionmentioning
confidence: 99%
“…Absence of freely moving parts, in conjunction with the capacity for partial MT closing and simple design represent advantages, especially in the biomedical field where biological cells should not to be destroyed (squeezed) during pumping. Johnson et al [3] proposed a MT pump based on a polydimethylsiloxane (PDMS) substrate with microvalves (throttles) and a glass membrane covered with piezoelectric (PZT) actuators. They used three PZT actuators and achieved pumping through appropriate sequential actuation of the PZTs.…”
Section: Introductionmentioning
confidence: 99%